Biosocial Determinants of Age at Menarche among Secondary School Girls in Benin City, Nigeria - Lokor O, Yovwin D. G, Okonkwo C. A (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the age at menarche among secondary school girls in Benin City and to establish biosocial determinants of menarcheal age. Method: Students at Benin City’s secondary schools were the focus of this descriptive study. Self-administered questionnaires that had been pretested were used to gather data. The height, weight, BMI, and mid-arm circumference of the study population were also measured. Menarchal age was compared to several measures of socioeconomic status. Results: Of the 1830 participants, 72.2 percent had already had their first period. The population’s average age at menarche was 12.72 1.24 years. When looking at the period from 1979 to 2009, a decrease of 3.3–4.3 months per decade was seen. Depending on the parents’ social status, women’s menarcheal ages range from as young as 12.3 years old to as old as 14.09 years old (P = 0.000), with 12.3 years old being the lowest and 14.09 years old being the highest. Conclusion: The age at menarche in Benin City school girls is 12.72 ± 1.24 years. There has been a decline in the menarcheal age compared to previous studies. The socioeconomic and nutritional status influence the age of menarche.